Pengaruh Merek, Harga dan Promosi terhadap Minat Gadai Emas Pada PT. Bank Syariah Indonesia Kantor Cabang Lombok Pancor - Abdul Hanan; Muhammad Sapwan; Muh. Khairul Fatihin (Jurnal Literasi Akuntansi, 2026)
Purpose: This study aims to examine the influence of brand, price, and promotion on customer interest in using gold pawn products at Bank Syariah Indonesia (BSI) KCP Pancor. The research seeks to identify which factors most strongly drive customers’ decisions to engage with Islamic pawn financing services, contributing to a deeper understanding of consumer behavior in Islamic banking. Method: A quantitative approach with an associative causal design was employed. The study involved 100 respondents selected through purposive sampling. Data were collected using a structured questionnaire based on a five-point Likert scale. The analysis utilized multiple linear regression supported by validity and reliability tests, classical assumption tests, the t-test, F-test, and coefficient of determination (R²) analysis. Finding: The results reveal that brand has no significant influence on customer interest, while price and promotion have significant and positive effects. The coefficient of determination (R²) of 0.349 indicates that 34.9% of customer interest is explained by brand, price, and promotion, while the remaining 65.1% is affected by other variables not included in this model. These findings demonstrate that practical factors, such as competitive pricing and effective promotional strategies, play a more dominant role in shaping customer preferences for Islamic gold pawn products. Novelty: This study provides empirical evidence that in the context of Islamic banking, customer interest is more strongly influenced by tangible benefits such as pricing and promotional appeal than by brand image. It highlights a behavioral shift among customers who prioritize economic and informational value over symbolic brand perception, offering new insights for Islamic financial institutions to refine their marketing strategies.